Analisis Penerimaan SIDJP Menggunakan Technology Acceptance Model (TAM) Pada KPP Pratama Mojokerto - Bagus Priyambada; Ari Kusyanti; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The presence of information systems ideally make the job easier and faster, especially SIDJP (Sistem Informasi Direktorat Jenderal Pajak) in KPP Pratama Mojokerto. Based on the observation of the researcher, KPP Pratama Mojokerto had problems in the acceptance and the use of SIDJP. This study aims to determine the factors that influence the acceptance of SIDJP in KPP Pratama Mojokerto by adopting the theory of Technology Acceptance Model (TAM), this study used four variables, they are Perceived Ease of Use, Perceived Usefulness, Behavioral Intention, and Actual System Use. The data was collected using a paper based questionnaire and distributed directly to 83 respondents who are users of SIDJP in KPP Pratama Mojokerto. Then, the data was analyzed using descriptive statistical analysis and linear regression analysis. The result of analysis shows that Perceived Ease of Use has the lowest ideal percentage value compared with Perceived Usefulness, Behavioral Intention, and Actual System Use. The results also showed that Perceived Ease of Use positively affect Perceived Usefulness, Perceived Usefulness and Perceived Ease of Use have positive effect on Behavioral Intention, and Behavioral Intention has positive affect on Actual System Use.